AB0462 Large vessel vasculitis refractory to conventional therapy. experience with tocilizumab. (23rd January 2014) - Sala, L.; Perez, S.; Fernandez, A.; Humbría, A.; Vicente, E.; Llorente, I.; García de Vicuña, R.; Castañeda, S.
Abstract : Background: Large vessel vasculitis (LVV) are a group of granulomatous inflammatory diseases affecting the wall of great vessels, which include Takayasu arteritis (TA) and giant cell arteritis (GCA). The standard treatment of both entities is based on glucocorticoids (GC) and immunosuppressants (IS). In recent years, alternative therapies for cases that do not respond to the combination of GC and IS have been tested. Among these, TNF antagonists and the receptor antagonist of IL-6 (tocilizumab, TCZ) have shown greater efficacy. Recently, we have revised all the patients diagnosed of LVV and treated with anti-TNF and TCZ in our hospital. Objectives: To describe our experience with 3 cases of refractory LVV treated successfully with TCZ. Methods: Case 1 . Asixteen year-old girl with TA who presented severe involvement of thoracic and abdominal aorta and also carotid artery. She was refractory to high-dose GC combined with methotrexate (MTX) at doses up to 25 mg/w and had a partial response to adalimumab (40 mg/15 days). In January 2012, off-label TCZ (8 mg/kg) was initiated with immediate response, allowing steroid tapering to 7.5 mg/d and soon achieving remission, confirmed by PET-CT, which is maintained at 1-year follow-up. Case 2. Sixty-five year-old woman with GCA confirmed by temporal artery biopsy in 2001. Initial high dose prednisone on monotherapy was effective, but flared when tapering under 10mg. Subsequent association of azathioprine was ineffective. MTX, leflunomide and cyclophosphamide were also tested without adequate response. In November 2010 she was treated with etanercept with good initial response but secondary loss of efficacy. In February 2012 TCZ 8 mg/kg was started with very good clinical and analytical responses. Case 3 . Seventy-four year-old female diagnosed of GCA, histologically confirmed, in 2006. Good initial control was obtained under standard prednisone protocol, but relapse when tapering. Several IS and biologics were tested: MTX 10 mg/w, withdrawn due to hepatotoxicity, and successive treatment with infliximab, rituximab (2 cycles) and abatacept, that proved to be ineffective. In 2010, TCZ was started (560 mg[SC1] /4 weeks) with good clinical and analytical control from the beginning. Results: We report 3 patients with poor response to GC, synthetic IS and some biologics, TNF antagonists, abatacept and rituximab, who responded well to treatment with TCZ, without any clinically relevant adverse events to date. Therapeutic alternatives for LVV patients who fail to TNF antagonists are under discussion. Usefulness of anti-TNF in TA is already known, but results seem not so good for GCA. By contrast, TCZ shows a good safety profile and more favorable outcomes in literature, though published studies are still scarce. Conclusions: In our experience treatment with TCZ has proven to be a valuable and safe alternative in LVV irresponsive to corticosteroids, synthetic immunosuppressive drugs and biologics such as rituximab and anti-TNF. Our small series of cases support TCZ effectiveness. However, larger and multicentric studies are needed to confirm these preliminary findings. Acknowledgements: L Sala and S Perez have contributed equally to this work. Disclosure of Interest: None Declared